Tomato transcriptional repressor SlBES1.8 influences shoot apical meristem development by inhibiting the DNA binding ability of SlWUS. (1st March 2022) - Su, Deding; Wen, Ling; Xiang, Wei; Shi, Yuan; Lu, Wang; Liu, Yudong; Xian, Zhiqiang; Li, Zhengguo
Significance Statement: The development of plant shoot apical meristems (SAMs) is accurately controlled by WUSCHEL (WUS), while the co‐regulators of WUS still need to be discovered. We identified a tomato ( Solanum lycopersicum ) transcriptional repressor, SlBES1.8, and found that it can interact with WUS and inhibit WUS–DNA binding to enlarge SAM size, which further results in an increase of floral organ numbers and changes in fruit shape. Thus, SlBES1.8 is a novel co‐regulator of WUS, contributing to the regulation of SAM development. SUMMARY: As the reservoir of pluripotent stem cells, the shoot apical meristem (SAM) is responsible for the production of aboveground plant organs including flower and fruit. The stem cell pool is dramatically influenced by a conserved negative feedback circuit between WUSCHEL (WUS) and CLAVATA (CLV). Numerous studies have focused on the functional mechanism of WUS in maintaining SAM development over the past few years, while the co‐regulators of WUS remain to be discovered. Here, we identified a tomato ( Solanum lycopersicum ) BES1 transcription factor, SlBES1.8, that is specifically expressed in the SAM and flower and functions as a transcriptional repressor. Overexpression of SlBES1.8 resulted in enlarged SAM and extra floral organs in tomato, which eventually led to the formation of pepper‐like fruit with increased soluble sugar and organic acid contents. Direct regulatory effects of SlBES1.8 on the CLV–WUS signaling cascade were not observed; instead, protein–protein interaction between SlBES1.8 and SlWUS was confirmed and the crucial interaction domains were identified. As a result, this heterodimerization significantly repressed the transcriptional regulation ability of SlWUS by inhibiting SlWUS binding to the promoter fragments of CLV3 and downstream genes. Taken together, our findings suggest that SlBES1.8 serves as a novel co‐regulator of SlWUS to influence the development of the SAM.